Ecological and economic efficiency of growing on dark gray soils of bean-cereal grasses - Uliana Karbivska; Yevheniia Butenko; Valentyna Nechyporenko; Olena Shumkova; Viktoriia Shumkova; Dmytro S. Tymchuk; Nataliya Tymchuk; Dmytro Litvinov; Anna Hotvianska; Valentina Toryanik (Agraarteadus, 2022)

(untitled)
The efficiency of growing leguminous and cereal agrophytocenoses (Trifolium pratense and Medicago sativa sown with the addition of Bromus inermis, Lolium multiflorum, Festuca rubra), highlighted their economic and energy advantages over cereal grasses. The article presents the results of the study of the influence of grass mixtures on the main indicators of the efficiency of growing sowing phytocenoses during haymaking in the Carpathians on dark grey soil. Growing agrophytocenoses without mineral fertilizers ensures the maintenance of 370–520 € ha–1 of net profit, with the profitability of 151–187%, the cost of 1 ton of feed units – 56.7–66.7 €, bioenergy coefficient – 2.5–2.9, energy efficiency ratio – 5.8–6.5 and energy consumption per 1 ton of feed units – 4.0–4.7 GJ. The cultivation of alfalfa-cereal grasses is ensured on dark-wet soil with three years of use of the best indicators of economic and energy efficiency. It was found that on both experimental bean-cereal grasses the highest efficiency is maintained when P60K60 is applied in combination with inoculation of seeds of bean strains of nodule bacteria.